2016
DOI: 10.1080/10615806.2016.1271876
|View full text |Cite
|
Sign up to set email alerts
|

Childhood exposure to emotional abuse and later life stress among Kenyan women: a mediation analysis of cross-sectional data

Abstract: Future research should investigate whether social integration, identity formation and self-esteem underlie observed dynamics in sub-Saharan Africa. Efforts to promote social integration and support should target children currently experiencing emotional abuse, and may include child-targeted high quality television programing and adult-targeted media and celebrity campaigns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 73 publications
1
12
0
Order By: Relevance
“…Recent studies have demonstrated that maternal maltreatment and exposure to violence are predictive of an increase in violent attitudes and tendencies toward children (Crombach & Bambonyé, 2015;Goodman, Hindman, et al, 2017). In Kenya, maladaptive family functioning and stress are pervasive, which in turn increases exposure to physical punishment and other forms of childhood adversity (Goodman, Gutarra, Gutarra, Billingsley, Keiser, & Gitari, 2017;Oburu & Palmérus, 2003). The psychosocial mechanisms for the transmission of risk in the context of ACEs, and the investigation into potential mediators have primarily converged on maternal mental health, caregiving, social support and exposure to stress in HIC.…”
Section: Impact Of Maternal Adversity On Child Outcomesmentioning
confidence: 99%
“…Recent studies have demonstrated that maternal maltreatment and exposure to violence are predictive of an increase in violent attitudes and tendencies toward children (Crombach & Bambonyé, 2015;Goodman, Hindman, et al, 2017). In Kenya, maladaptive family functioning and stress are pervasive, which in turn increases exposure to physical punishment and other forms of childhood adversity (Goodman, Gutarra, Gutarra, Billingsley, Keiser, & Gitari, 2017;Oburu & Palmérus, 2003). The psychosocial mechanisms for the transmission of risk in the context of ACEs, and the investigation into potential mediators have primarily converged on maternal mental health, caregiving, social support and exposure to stress in HIC.…”
Section: Impact Of Maternal Adversity On Child Outcomesmentioning
confidence: 99%
“…Given that survivors still endorsed PTS symptoms in adulthood, the findings attest to the significance of the timing of adverse events on PTS symptoms in later life (Dunn et al, 2017). The study therefore accounted for the developmental impact of multiple ACES on PTS symptoms, which in itself goes beyond existing findings that tend to focus on responses to a single type of ACE only (Goodman et al, 2017). An additional implication of the current study is that it identifies that PTS symptoms arising from ACEs have a significant role to play in psychological adjustment, alongside the characteristics of the events themselves.…”
Section: Discussionmentioning
confidence: 86%
“…Wider evidence is limited, as existing studies tend to focus on direct predictors of PTS symptoms (Elklit, Christiansen, Palic, Karsberg, & Eriksen, 2014), or focus on other mediators of negative outcomes following ACEs, such as rumination on anxiety symptoms (Kim, Jin, Jung, Hahn, & Lee, 2017). In addition, some existing ACE studies address only one type of childhood trauma such as emotional abuse (Goodman, Gutarra, Billingsley, Keiser, & Gitari, 2017) rather than accounting for the number of different types of ACEs that people may experience.…”
Section: Introductionmentioning
confidence: 99%
“…In a study among mothers in semi-rural Kenya, perceived stress was shown to be related to emotional abuse during childhood. 38 Compared to women who reported their religion as Protestant, NPD K6 scores were lower among women who reported their religion as "Other". The "Other" category, comprised of two African independent churches, Nomiya and Roho, are based in Christianity but have broken off with other Christian or Protestant denominations.…”
Section: Discussionmentioning
confidence: 91%